A modified protocol for isolation and purity evaluation of a staphylococcal acidic polysaccharide by chromatography and capillary electrophoresis - Krevvata, M. I.; Afratis, N.; Spiliopoulou, A.; Malavaki, C. J.; Kolonitsiou, F.; Anastassiou, E.; Karamanos, N. K. (Biomed ChromatogrBiomed Chromatogr, 2011)
The extracellular slime of Staphylococcus epidermidis contains, amongst various macromolecules, an acidic polysaccharide (PS) of a molecular mass of 20 kDa with significant antigenic and biological properties. The isolation procedure used so far includes multiple fractionations in anion-exchange chromatographic columns before its final purification by gel filtration chromatography. This protocol is laborious, time-consuming and includes the risk of unnecessary loss of PS quantities. Because of the significance of this PS, a modified protocol resulting in an easier and quicker isolation procedure was developed. Furthermore, identification, purity, charge density and molecular integrity of the isolated polysaccharide were evaluated by a reverse-polarity capillary electrophoresis method.
Keywords: Electrophoresis, Capillary/*methods; Formates/chemistry; Hydrogen-Ion Concentration; Polysaccharides, Bacterial/chemistry/*isolation & purification; Staphylococcus epidermidis/*chemistry